(untitled) (Raparin Journal of Humanities (RJH), 2021)
This research dedicated to types of poem، it was written while he was prison، Firstly، we mentioned about definition and history type of resistance، secondly، we discussed about reasons of beginning this type of poetry، in a section we discussed about language and types of express and these topics that resistance poem expresses، and finally we discussed shortly of Shahid Mala Ali’s life with some examples of his poem which it is full of resistant and victory، also we gained benefits from some sources.